Engineering a Topic Modeling System: Architecture, Process, and UML Modeling (Indian Journal of Software Engineering and Project Management (IJSEPM), 2026)
Software engineering is a discipline that uses Unified Modelling Language diagrams, which are among the most widely accepted standards for visualising object-oriented design models. Using UML diagrams, system and application requirements are specified by providing understandable models of the objects involved. Thus, the goal of this study is to describe how software engineering is applied to our topic modelling system. This study describes the software engineering process from story to system testing, and then supports it with a UML diagram for clarity. This paper demonstrated empirically how software engineering principles are integrated into a system using Latent Dirichlet Allocation (LDA). Several engineering operations were performed on data from a group of websites, yielding measurable, verifiable results that support the system's reliability.